(3QSGdI aj Mjd GSJfHGW GdMSGHs
(3ChdgG (B:s
(3HYO GdHSedI GWGd Gddg HbGAc jG Hf GdSGOI GdCNjGQ afbhd Ef GdMjdI aj GSJfHGW Yde GdMSGH GdeVeQ deSGFdI eUQ ShGg dGjXgQ ajg ddeVeQ Cfg GdNHQ aj LhGHI s
(3BNQgG (B:s
(3aeG NQL agh eG cGf aj Gdjejf eG de jJe agh eG cGf aj GdjSGQ hGdHGbj HYOgG ef GdCUd agh eG cGf aj GdbdH s
(3Vef eLehY , JQJjHgG (B: 3s
(3HgG fXGe GdJYbjHIs
(3hjJdhg ahGFO aj Yde GdgfOSI hGdCTcGds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdQjGVjGJs